Moroccan EFL Students’ Attitudes toward Collaborative Learning in Argumentative Writing - Choujaa, Mohamed; Hellalet, Nadia; Echcharfy, Mouhssine (International Journal of Language and Literary Studies, 2026)
In response to the restrictions of the teacher-centred approach, collaborative learning has been introduced as a more inclusive pedagogy that can promote students’ classroom interactions, active engagement, and learning satisfaction. Based on this, the current study seeks to explore Moroccan EFL public high school students’ attitudes toward collaborative learning in argumentative writing. In light of a mixed-method approach, the study employed a questionnaire to gather data from 158 students across three public high schools in Casablanca. This is followed by a semi-structured interview with 12 participants for a deeper understanding of the issue. The results displayed that participants held an overall positive attitude toward collaborative writing, which they mainly attributed to its effectiveness in providing a space for sharing opinions, exchanging feedback, and forging meaningful relationships. However, low levels of English language, noise, and unequal participation were identified as key barriers to effective group argumentative writing. These results suggest that collaborative writing must be effectively integrated into Moroccan EFL classes to enhance students’ argumentative writing performance.